A literature review about the impact of climate change on malaria in South Sudan - Diana A. Androga (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
Mortality from malaria remains high in Africa despite constant efforts to combat the disease. By the end of 2018, fatalities were estimated to be 380,000 per year. This literature review covers papers on the management of malaria and the impact of climate change on the disease in South Sudan. PubMed and the South Sudan Medical Journal website were searched using the MeSH terms (Medical Subject Headings): malaria, prevalence, epidemiology, diagnosis, medication, prevention, strategies, policies, South Sudan, chemoprophylaxis, immunity. Fifteen studies were included in the final review. Information was extracted on climate change, mosquito activity and management of malaria. Seeking improvements in the treatment and prevention of malaria is an on-going task. New strategies are needed aimed at tackling climate change and the elimination of the disease.